Policy Options to Mitigate Political Risk and Attract FDI - Kher, Priyanka (World Bank, Washington, DC, 2020)
Political risks covers a wide range of issues, and this note focuses on a subset of political risk: the risks that arise from government actions, whether political or regulatory, that can affect the profitability of an investment in a foreign country. Policies adopted and implemented by governments can directly mitigate these risks. Bad governance and economic crises are two big drivers of political risk. Both are currently prevalent globally, but especially in developing countries. The purpose of this note is to summarize how political risk caused by government actions can impact foreign investment, and what tools countries can use to manage and mitigate such risks.